CGIAR Food Systems Accelerator: kick-off and onboarding workshop - complementary report on reflections on the accelerator and technical assistance design and implementation, Kigali, Rwanda, 22-24 February 2023 - Dahl, Hauke; Sartas, M. (Colombo, Sri Lanka: International Water Management Institute (IWMI), 2023)
Food system accelerators are programs that support agribusinesses in scaling their innovations to address the challenges and opportunities in food and agriculture systems. They typically provide a combination of technical assistance, mentoring, networking, and access to finance to help agribusinesses grow and achieve positive social and environmental impact. Food system accelerators are emerging as a promising approach to foster climate-smart innovation and transformation in agri-food systems, especially in developing regions where climate change, population growth, food insecurity, and malnutrition pose serious threats. Climate-smart innovation can enhance the efficiency, resilience, transparency, and inclusiveness of agri-food value chains, as well as improve the livelihoods of smallholder farmers and consumers. However, scaling climate-smart innovations in agri-food systems is not easy. It requires a deep understanding of the complex and dynamic context of agri-food systems, as well as the needs and preferences of different actors and stakeholders. It also requires collaboration and coordination among various actors, such as researchers, entrepreneurs, investors, policymakers, extension agents, and end-users. Moreover, it requires overcoming various barriers and risks, such as lack of infrastructure, skills, data, regulation, trust, and financing. To address these challenges, food system accelerators leverage the expertise and network of CGIAR, a global research partnership for a food-secure future. CGIAR has a portfolio of innovations that span various domains of agri-food systems, such as crop improvement, livestock production, natural resource management, nutrition, gender, policy, and markets. CGIAR also has a strong presence and partnership in many developing countries where agri-food systems face the most pressing problems. One example of a food system accelerator is the CGIAR Food Systems Accelerator Programme (FSA), launched in partnership with 2SCALE in 2022. The FSA aims to support at least 30 agribusinesses in East and Southern Africa by 2024 with scaled-up climate-smart innovations that support diversification, intensification, and risk management of maize mixed systems. The FSA provides tailor-made support to selected agribusinesses under four priority innovation themes: mechanization and irrigation, conservation agriculture, nutrition-sensitive climate-smart agriculture, and agricultural risk management. The FSA also offers de-risking grants and matchmaking with private investors for follow-on capital. In February 2023, CGIAR FSA organized the initiation workshop for the first successful group of startup businesses at Norrsken House, Kigali, Rwanda. This report has its focus on participants’ reflections on the food system accelerator process and the way forward.